The Burden of Cardiovascular Diseases Due to COVID-19 Pandemic - Hussain, Md Sadique; Sharma, Ganesh (The Thoracic and Cardiovascular Surgeon, 2022)
The coronavirus disease 2019 (COVID-19) is an infection caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that produces respiratory symptoms and has serious consequences for people's cardiovascular systems (CVS). It is a severe issue and a major task not only for health care experts but also for governments to contain this pandemic. SARS-CoV-2 is the seventh member of the human coronavirus family to be implicated in this zoonotic outbreak. COVID-19's CV interactions are comparable to those of SARS-CoV, Middle East respiratory syndrome (MERS-CoV), and influenza. Those who have COVID-19 and underlying cardiovascular diseases (CVDs) are at a higher risk of serious illness and mortality, and disease has been linked to several direct and indirect CV consequences. COVID-19 causes CVDs such as arrhythmias, cardiac arrest, cardiogenic shock, myocarditis, stress-cardiomyopathy, and acute myocardial damage (AMD) as a consequence of acute coronary syndrome. The provision of CV care may expose health care professionals to risk as they become hosts or vectors of viral transmission. It binds to the angiotensin-converting enzyme receptor, causing constitutional and pulmonary signs in the beginning, and then as the infection advances, it affects other organs such as the gastrointestinal tract, CVS, neurological system, and so on. COVID-19 mortality is increased by underlying CVDs comorbidities.
Keywords: cardiogenic shock; stress-cardiomyopathy; ACE-2; mortality